2021
DOI: 10.1016/j.pmedr.2021.101628
|View full text |Cite
|
Sign up to set email alerts
|

Long-term physical activity outcomes in the Seamos Activas II trial

Abstract: Highlights Latinas received an Original or Enhanced physical activity (PA) intervention. Gains in PA at six months were maintained at 12 months for both interventions. Minutes of PA did not significantly differ between the two conditions over time. The Enhanced group was more likely to meet national PA guidelines at 12 months. Enhancements (theory, texting) can help high risk populations meet PA guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The outcomes of the study by Chang et al (45) which included elements of the SCT in order to guide the intervention, showed that participants in the intervention group reported significant less depression symptoms than the control group. Results from two of the six included studies (48,49) showed no significant group differences in depression symptoms. Jones et al (46) who investigated whether participants' mental health was associated with the rate of attendance and engagement with the behavioral weight management program (WW) and trial (WRAP) found that a reduction in depression symptoms was associated with higher participation rates in WW sessions.…”
Section: Main Findings Of the Studymentioning
confidence: 87%
See 4 more Smart Citations
“…The outcomes of the study by Chang et al (45) which included elements of the SCT in order to guide the intervention, showed that participants in the intervention group reported significant less depression symptoms than the control group. Results from two of the six included studies (48,49) showed no significant group differences in depression symptoms. Jones et al (46) who investigated whether participants' mental health was associated with the rate of attendance and engagement with the behavioral weight management program (WW) and trial (WRAP) found that a reduction in depression symptoms was associated with higher participation rates in WW sessions.…”
Section: Main Findings Of the Studymentioning
confidence: 87%
“…On top of that, it underlines the relevance of the inclusion of cognitive features in obese treatment in order to achieve changes in the cognitive distortions, experienced by individuals with obesity. In contrast to such interventions, those focusing primarily on education through materials, i.e., non-interactive strategies showed less success in reducing depression symptoms (48,49). Thus, interactive modules as used in the SHED-IT recharge intervention, conducted by Young et al (42), that combined activities with educative materials, seemed to be particularly effective in the reduction of depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations